The consumption of commercially valuable fish by pinnipeds in Northwest Icelandic waters - Nebel, Sarah Elizabeth (2011)
Verkefnið er unnið við Háskólasetur Vestfjarða Fisheries are one of the most valuable exports for Iceland. In order to protect valuable fish stocks, it is necessary to understand their ecological context. Interspecific competition between humans and pinnipeds for commercially valuable fish requires consideration when managing fisheries and marine resources. The foundation for the study of interspecific competition lies in the analysis of the overlap in prey consumption between competing predators. This requires an understanding of the consumption of prey by predatory species of interest. While information regarding the fisheries is widely available, the knowledge of seal diets in Iceland is limited. This study uses the identification of fish otoliths and other hard parts, invertebrate carapaces, and squid beaks to assess the diets of the native common seal (Phoca vitulina) and the grey seal (Halichoerus grypus), as well as the winter-visiting harp seals (Pagophilus groenlandicus). Seals were collected by fishers and hunters, either as by-catch in gill nets or shot, during the months of March to September 2010. Sixty-four common seal, 19 grey seal and 13 harp seal stomachs were analyzed for prey contents. Common seal stomachs contained Atlantic cod (Gadus morhua) and Atlantic wolffish (Anarhichas lupus) in the highest quantities of estimated wet weight (60.7% and 20.8%, respectively), while grey seal stomach contents contained Atlantic wolffish (67.9%) and Atlantic cod (23.9%) and harp seal samples contained haddock (Melanogrammus aeglefinus) (36.0%), Atlantic cod (33.2%) and capelin (Mallotus villosus) (17.5%). Analysis of the overlap with fisheries determined that of the 17 fish species of economic value that are targeted by commercial fisheries, nine were found in the stomachs of common seals, seven in the stomachs of grey seals, and six in the stomachs of harp seals. Harp seals were the only seal species analyzed in this study found to consume a by-catch species of economic value to the Icelandic fishery; ...